The asymmetric synthesis of (2R,3R)- and (2R,3S)-3-methyl-aspartates via an enantiodiscrimination strategy - Bull, S; Davies, S; Garner, A; Mujtaba, N (2001)
The enolate of (S)-N,N′-bis-(p-methoxybenzyl)-3-isopropylpiperazine-2,5-dione exhibits high levels of enantiodiscrimination towards racemic 2-bromo-propionate esters to afford adducts containing two new stereogenic centres which may be deprotected to afford (2R,3R)-3-methyl-aspartates or epimerised and then deprotected to afford (2R,3S)-3-methyl-aspartates as single diastereoisomers in high e.e.